(untitled) (Konturen, 2010)
The borders between autism and psychosis are determined by the position that the subject takes with respect to the entry into language during the mirror stage. An ethical choice on the part of the subject of the unconscious seems, very early in life, to determine the passage or the refusal of passage into the field of the Other. As a result of their experiences, certain children choose to reside in the present instant and to build their own space by surrounding themselves with objects, while other children take the risk of language and enter the time of the Other through which their history will be structured. We will address this question through consideration of the autobiographies of autistics and the clinical testimonies of psychotic patients.